2021
DOI: 10.1111/eos.12755
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and psychosocial correlates of oral hygiene practice among Indonesian adolescents

Abstract: Poor oral hygiene leads to poor oral health, which in turn has negative impacts on overall health and quality of life. This study aimed to evaluate the prevalence and associated factors of oral hygiene practice among school‐going adolescents in Indonesia. Secondary analysis of cross‐sectional, nationally representative data from the 2015 Indonesia Global School‐based Health Survey, covering 11,142 students aged 11‐18 years, was performed. Multiple logistic regression was employed to explore associations betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
1
8
3
Order By: Relevance
“…It was found that 32.6% of Chinese adolescents brushed their teeth twice a day, which meant that more than 2/3 of adolescents cleaned their teeth once a day or less often. Compared to the ndings of other studies on similarly aged subjects, the nding of this study is higher than that in Iran (20.1%) 22 , but much lower than that in Malaysia (87%) 23 , Indonesia (89.2%) 24 , North America (65%) 25 and even most middle-income or low-income countries (70%) 26 .…”
Section: Discussioncontrasting
confidence: 82%
“…It was found that 32.6% of Chinese adolescents brushed their teeth twice a day, which meant that more than 2/3 of adolescents cleaned their teeth once a day or less often. Compared to the ndings of other studies on similarly aged subjects, the nding of this study is higher than that in Iran (20.1%) 22 , but much lower than that in Malaysia (87%) 23 , Indonesia (89.2%) 24 , North America (65%) 25 and even most middle-income or low-income countries (70%) 26 .…”
Section: Discussioncontrasting
confidence: 82%
“…Furthermore, a lower prevalence of adolescents engaging in teeth cleaning more than once daily has been documented among adolescents in Malta and some Eastern and Southern European countries ( 28 ). On the other hand, higher values of 80–89% had been reported in Switzerland ( 28 ) and 89.2% noted in Indonesia ( 29 ). The differences in the figures reported in the studies can be attributed to the different social classes of the adolescents and the socioeconomic categories of the various countries studied as well as the age groups of the adolescents.…”
Section: Discussionmentioning
confidence: 88%
“…Studies in Mexico have reported prevalence ranging from 49.8% in Campeche [ 29 ], 56.3% in Sinaloa [ 40 ], to 81.7% also in Campeche [ 15 ]. In other countries, very low percentages of toothbrushing in schoolchildren have been reported, such as in Iran (18.0%) [ 26 ], Palestine (19.7%) [ 41 ], or China (26.3%) [ 42 ], to prevalence numbers higher than 80%, such as in Norway [ 27 ], Indonesia [ 43 , 44 ], and Brazil [ 23 ]. Differences may be due to different circumstances such as the specific age of the children and adolescents in the studies, and even the economic development of the communities or countries where research was conducted.…”
Section: Discussionmentioning
confidence: 99%